Metabolic syndrome in chronic obstructive pulmonary disease - Pasha, M. D. Majeed; Salimath, Shivalingaswamy; K. N., Mohan Rao; H. J., Gayathri Devi; Aneja, Anshum; Padmaja, Mantha Satya; Halappa, Sujith (International Journal of Advances in Medicine, 2018)
Background: COPD (Chronic obstructive pulmonary disease) is considered as a systemic disease due to associated systemic inflammation which can manifest as metabolic syndrome or its component illnesses. This study was undertaken to determine the proportion of metabolic syndrome in patients with COPD. Methods: 51 patients with COPD were compared with equal number of age and gender matched controls. GOLD (Global Initiative for Chronic Obstructive Lung Disease) criteria were used for diagnosing COPD. Metabolic Syndrome (MS) was diagnosed based on modified NCEP:ATP III criteria (National cholesterol education Program Adult Treatment Panel III). Subjects were evaluated for hypertension, WC, FBS, and serum triglycerides and serum HDL (High-density lipoprotein) to diagnose MS. Results: Metabolic syndrome was diagnosed in 16 (31.4%) patients with COPD and in 8 (15.7%) controls. The proportion of individual parameters of MS in cases and controls was as follows: DM in 19 (37.3%) cases and 13 (25.5%) controls, hypertension in 21(41.2%) cases and 9 (17.6%) controls, low serum HDL in 31 (60.7%) cases and 22 (43.1%) controls increased WC in 14 (27.5%) cases and 7 (13.7%) controls and elevated serum TG in 12 (23.5%) cases and an equal number of controls. Conclusions: Metabolic syndrome and its parameters are more prevalent in COPD patients. Early detection and treatment of MS in COPD patients can prevent development of complications due to the combined effects of both diseases.